2020
DOI: 10.1098/rsob.200102
|View full text |Cite
|
Sign up to set email alerts
|

A self-assembled cylindrical platform for Plk4-induced centriole biogenesis

Abstract: The centrosome, a unique membraneless multiprotein organelle, plays a pivotal role in various cellular processes that are critical for promoting cell proliferation. Faulty assembly or organization of the centrosome results in abnormal cell division, which leads to various human disorders including cancer, microcephaly and ciliopathy. Recent studies have provided new insights into the stepwise self-assembly of two pericentriolar scaffold proteins, Cep63 and Cep152, into a near-micrometre-scale higher-order stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 103 publications
1
5
0
Order By: Relevance
“…To gain an overall view of how Cep63 and Cep152 are organized around a centriole, mCherry-Cep63-mGFP (i.e., the full-length Cep63 containing an N-terminally tagged mCherry and a C-terminally tagged mGFP 32 ; both mCherry and mGFP are monomeric) and mGFP-Cep152-mCherry constructs were expressed in U2OS cells after depleting the respective endogenous proteins by RNAi. 3D-structured-illumination microscopy (3D-SIM) showed that, in line with earlier findings 12 , 19 , Cep63 and Cep152 displayed distinguishable localization patterns around the longitudinal axis of a centriole within a confined volume of the inner PCM space (Fig. 1a and Supplementary Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…To gain an overall view of how Cep63 and Cep152 are organized around a centriole, mCherry-Cep63-mGFP (i.e., the full-length Cep63 containing an N-terminally tagged mCherry and a C-terminally tagged mGFP 32 ; both mCherry and mGFP are monomeric) and mGFP-Cep152-mCherry constructs were expressed in U2OS cells after depleting the respective endogenous proteins by RNAi. 3D-structured-illumination microscopy (3D-SIM) showed that, in line with earlier findings 12 , 19 , Cep63 and Cep152 displayed distinguishable localization patterns around the longitudinal axis of a centriole within a confined volume of the inner PCM space (Fig. 1a and Supplementary Fig.…”
Section: Resultssupporting
confidence: 89%
“…Remarkably, Cep63 and Cep152 can self-assemble into a radially aligned, submicrometer-scale, cylindrical structure in vitro in such a fashion that the N-termini of Cep63 and Cep152 are placed at the innermost and outermost regions, respectively, of the structure 12 . The dimensional and spatial organization of the in vitro Cep63•Cep152 self-assembly are comparable to the pericentriolar localization patterns of endogenous Cep63 and Cep152 17 19 . These findings indicate that, unlike other structural CC proteins, such as vimentin and keratin, which form elongated, cable-like filaments for physical strength, Cep63 and Cep152 possess distinct physicochemical properties that enable them to generate higher molecular weight (MW) complex(es) and construct a cylindrical self-assembly around a centriole.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Associated proteins Cep57 and Cep63, which bind to parental centriole microtubules and Cep152, respectively, indirectly assist in Plk4 loading to the centrosome ( Brown et al, 2013 ; Kim et al, 2019 ; Lukinavicius et al, 2013 ; Sir et al, 2011 ; Wei et al, 2020 ). Molecular assemblies of Cep57 and Cep63–Cep152 complexes generate a scaffold that is critical for centriole initiation and centriole duplication control ( Lee et al, 2020 ; Wei et al, 2020 ). While binding properties of Plk4 and its receptor molecules have been extensively dissected biochemically, their centrosomal organization, as well as the organization of Cep57 and Cep63, still requires dissection at high resolution.…”
Section: Introductionmentioning
confidence: 99%
“…While there is some data supporting the idea that centriolar CEP152/Asl, a major recruiter of PLK4 to the centriole (Hatch et al, 2010; Dzhindzhev et al, 2010; Cizmecioglu et al, 2010) may be organised in discrete compartments, the precise number and organisation of these compartments is unclear (Takao et al, 2019; Tian et al, 2021; Wainman, 2021; Gao et al, 2021; Tian et al, 2022; Wilmerding et al, 2023). Moreover, it has also been proposed that CEP152 may be able to self-assemble around the centriole as a continuous ring (Kim et al, 2019; Lee et al, 2020). Importantly, the reaction-diffusion models we have examined here will still break symmetry on a centriole surface comprising essentially any number of discrete compartments (Figure 5), but such compartmentalisation is not an essential requirement of our approach.…”
Section: Discussionmentioning
confidence: 99%